Biomimetic strategies for targeted nanoparticle delivery. Issue 1 (27th May 2016) - Dehaini, Diana; Fang, Ronnie H.; Zhang, Liangfang
Abstract: Nanoparticle‐based drug delivery and imaging platforms have become increasingly popular over the past several decades. Among different design parameters that can affect their performance, the incorporation of targeting functionality onto nanoparticle surfaces has been a widely studied subject. Targeted formulations have the ability to improve efficacy and function by positively modulating tissue localization. Many methods exist for creating targeted nanoformulations, including the use of custom biomolecules such as antibodies or aptamers. More recently, a great amount of focus has been placed on biomimetic targeting strategies that leverage targeting interactions found directly in nature. Such strategies, which have been painstakingly selected over time by the process of evolution to maximize functionality, oftentimes enable scientists to forgo the specialized discovery processes associated with many traditional ligands and help to accelerate development of novel nanoparticle formulations. In this review, we categorize and discuss in‐depth recent works in this growing field of bioinspired research.